A sustainable, cost-effective reinforced concrete portal frame for covering a large hall - Momen M. Ali; Hamdy M. Afefy; Abdelrhman B. Harraz (Academia Materials Science)
Selecting the most cost-effective main supporting system for large halls has a significant influence on the overall cost, particularly since the main supporting system is replicated several times. This choice can reduce the total quantity of materials used, such as aggregate, including both coarse and fine aggregate, helping to conserve natural resources. Additionally, reducing the amount of cement required also leads to a lower carbon footprint, contributing to a cleaner environment. In this study, we investigated different configurations of the portal frame, incorporating internal struts at the joints between girders and columns, utilizing broken girders, and employing broken girders with horizontal ties and hangers for spans of 12 m, 20 m, and 28 m. This approach is designed to identify the structural system that induces the lowest bending moments at critical sections of the portal frame under applied loads. Consequently, a 2D finite element simulation was conducted to model the different configurations of the analyzed frames using SAP2000. In total, 51 case studies were created, representing portal frames that employ the mentioned configurations. The findings indicate that a reinforced concrete portal frame featuring a broken girder with a horizontal tie is the most economical structural system. As a result, the quantity of material used could be reduced, yielding a cost reduction of 33% for a portal frame with a 12 m span. However, as the span of the frame increases, the amount of material saved decreases, with cost savings reaching up to 23% for a frame with a 28 m span.